Online Writing Teaching Strategies During Covid -19 Pandemic - Restia Apriani (CV. Tripe Konsultan, 2022)
The objective of this research was to find out the online writing teaching strategies during covid 19 pandemic. The research methodology used a qualitative descriptive method, while the information assortment methods utilized interviews, observation, and documentation. The subject of this research was the English teachers who taught at the seventh grade of MTSN1 Bandar Lampung.The result of this research found that there were several strategies used by teachers in teaching writing process including planning, drafting, editing and final version of online strategies during Covid-19 pandemic era. The first teacher used video as learning strategy and small group discuss strategy and from the second teacher used pictures as learning strategy and imaginary strategy in online writing teaching process including planning, drafting, editing and final version. The result showed that the strategies helped the teacher to teach writing online easier. The teacher was able to know the students` understanding of the materials and the students were able to do the assignment given by teacher. The students also gave good response to the teaching writing online strategies during Covid-19 pandemic.